(untitled) (应用人工智能研究, 2025)
With the rapid development of AI technology, its application in art creation is becoming more and more popular. An automatic generation system of AI art works can generate works of unique style and aesthetic value by means of deep learning algorithms. However, the question of creative ownership behind AI-generated works has always been ambiguous. In this paper, we discuss creative rights and aesthetic boundaries behind AI-generated works. However, there has not been a clear legal definition. In spite of this, AI’s automatic generation of artworks has become a major trend. At present there are no laws or regulations that stop the development of AI + art.. On the basis of the above results, we have developed an AI generation system. Using AI technology, it automatically generates artwork that creators want.In addition, the public often believes that the ownership of AI-generated artworks belongs to the AI platform. In fact, the AI system is merely an auxiliary tool, and the creative inspiration still comes from the author. Therefore, this system can generate a contract for the AI system platform to this AI system waive the copyright.Register your copyright on the website of the National Copyright Center to avoid legal disputes and protect the legitimate rights and interests of creators.